Clinical characteristics and 1‐year outcomes in hospitalized patients with heart failure with preserved ejection fraction: results from the China Cardiovascular Association Database‐Heart Failure Center Registry. (11th September 2022) - Cai, Anping; Qiu, Weida; Zhou, Yingling; Feng, Yingqing; Chen, Jiyan; Xia, Shuang; Li, Weimin; Liao, Yuhua; Li, Xinli; Zhou, Jingmin; Wang, Hua; Jin, Wei; et al.
Abstract: Aim: We aimed to evaluate clinical characteristics and 1‐year outcomes in hospitalized patients with heart failure with preserved ejection fraction (HFpEF) from China. Factors associated with outcomes (hospitalization for HF [HHF] and cardiovascular [CV] death) were assessed. Method and results: Data were from the China Cardiovascular Association (CCA) Database‐HF Center Registry. Between January 2017 and June 2021, 41 708 hospitalized HFpEF patients with 1‐year follow‐up from 481 CCA Database‐HF Center certified secondary and tertiary hospitals across overall 31 provinces of mainland China were included in this study. Of study participants (mean age 72.2 years, 49.3% female), 18.2% had HHF in prior 1 year and 55.8% had New York Heart Association class III/IV. Median left ventricular ejection fraction was 59%. Ischaemia (26.6%), infection (14.4%) and arrhythmia (10.5%) were the three most common precipitating factors for index HHF. Nearly 67.4% had ≥3 comorbidities. Hypertension (65.2%), coronary heart disease (60.3%) and atrial fibrillation (41.2%) were the three most common comorbidities. Device and medication therapy non‐compliance with current HF guideline recommendation was observed. The 1‐year rate of clinical outcomes was 16.4%, the 1‐year rate of HHF was 13.6% and CV death was 3.1%. Factors associated with clinical outcomes included HHF in prior 1 year, serum level of sodium <135 mmol/L and N‐terminal pro‐B‐type natriuretic peptide >1800 pg/ml. Conclusion: Patients with HFpEF from China were characterized by high comorbid burden and high 1‐year risk of HHF and CV death. Immediate efforts are needed to improve HFpEF management in China.